2020
DOI: 10.1371/journal.pbio.3000684
|View full text |Cite
|
Sign up to set email alerts
|

Precise genomic mapping of 5-hydroxymethylcytosine via covalent tether-directed sequencing

Abstract: 5-hydroxymethylcytosine (5hmC) is the most prevalent intermediate on the oxidative DNA demethylation pathway and is implicated in regulation of embryogenesis, neurological processes, and cancerogenesis. Profiling of this relatively scarce genomic modification in clinical samples requires cost-effective high-resolution techniques that avoid harsh chemical treatment. Here, we present a bisulfite-free approach for 5hmC profiling at single-nucleotide resolution, named hmTOP-seq (5hmC-specific tethered oligonucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…The previous base-resolution mapping of 5hmC allowed for the determination of the surrounding base composition of 5hmC sites in mouse ESCs. 22 We aligned our 5hmC sites in CG context and examined the base compositions (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous base-resolution mapping of 5hmC allowed for the determination of the surrounding base composition of 5hmC sites in mouse ESCs. 22 We aligned our 5hmC sites in CG context and examined the base compositions (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, there are two strategies, which are the selective enrichment-based profiling or deamination based single-base resolution sequencing methods. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] While the current applications of these methods have provided key information about the distribution of 5hmC and its functional insights, there are major shortage for both strategies. The lack of single-base resolution information of the profiling strategy limited its application in detailed 5hmC location context while the single-base resolution method is limited by its high sequencing cost.…”
mentioning
confidence: 99%
“…The second important milestone of our study is the first known to date demonstration that 5hmC profiling in maternal cfDNA can accurately inform on fetal karyotype. The hmTOP-seq method [25], which covalently targets 5hmC residues, enabled the construction of genome-wide 5hmC maps of relatively low 5hmC levels in CV samples and cfDNA. Most importantly, we observed that hmTOP-seq was most discriminatory in detection of T21 fetuses independently of fetal fraction.…”
Section: Discussionmentioning
confidence: 99%
“…For profiling of uCGs and 5hmCGs we employed our recently developed uTOP-seq and hmTOP-seq strategies, respectively, which assess the modification status of genomic CG sites through selective covalent coupling of a priming oligonucleotide to azide-modified CGs and their subsequent sequencing [24,25]. By leveraging the high robustness of covalent derivatization and the sensitivity of such targeted sequencing we successfully adapted both strategies for the analysis of nanogram quantities of cfDNA.…”
Section: Genome-wide Ucg and 5hmcg Patterns Suggest Strong Fetal Contmentioning
confidence: 99%
See 1 more Smart Citation